Fluorescence-detected magnetic field effects on radical pair reactions from femtolitre volumes. - Dodson, C; Wedge, C; Murakami, M; Maeda, K; Wallace, M; Hore, P (2015)
We show that the effects of applied magnetic fields on radical pair reactions can be sensitively measured from sample volumes as low as ∼100 femtolitres using total internal reflection fluorescence microscopy. Development of a fluorescence-based microscope method is likely to be a key step in further miniaturisation that will allow detection of magnetic field effects on single molecules.